How and when perceived COVID-19 crisis strength impacts individuals' life satisfaction and sleep quality: A moderated mediation model - Lan, Yuanyuan; Han, Changlin; Liu, Xiaotong; Cao, Qinqin; Chen, Siyuan; Xia, Yuhuan (Frontiers in Public Health, 2022)
The COVID-19 pandemic has caused millions of deaths, seriously hampering people's lives and their productivity. Drawing on social information processing theory, this research developed a moderated mediation model to investigate the influence of perceived COVID-19 crisis strength on individuals' well-being. The results from a sample of 441 suggest that individuals' perceived COVID-19 crisis strength indirectly affects their life satisfaction and sleep quality via their perceived risk of being infected. Moreover, both individuals' trust in local government and mindfulness trait can buffer the positive effect of perceived COVID-19 crisis strength on their perceived risk of being infected. At the same time, they also buffer the indirect impact of individuals' perceived COVID-19 crisis strength on life satisfaction and sleep quality through perceived risk of being infected. This research provides several practical implications for governments and individuals to mitigate the negative influences of the COVID-19 pandemic and help individuals boost life satisfaction and sleep quality.